Chinese herbal medicine to treat urolithiasis in a patient with right flank pain and hematuria: A case report. (February 2018) - Lai, Hsiang-Chun; Lin, Hung-Jen; Huang, Sheng-Teng
Abstract: Objective: Urolithiasis is a common medical condition affecting the urinary tract. Typical symptoms reported by patients include colic pain and hematuria. Some patients may undergo surgical intervention or lithotripsy to remove the stones. In this case, we demonstrated that Chinese herbal medicine (CHM) was an effective modality to remove stones in a patient with urolithiasis. Clinical features and outcome: A 47-year-old man suffered from right flank pain and hematuria for three months and was diagnosed with an upper third ureteral stone obstruction with right hydronephrosis. He had received extracorporeal shock wave lithotripsy (ESWL) three times before his first CHM visit, but it was unsuccessful. Therefore, he sought CHM for further intervention. His symptoms subsided, and the image study showed complete removal of the ureteral stone after regular therapy with Zhi Bai Di Huang Wan ( ) combined with Lygodii spora ( ), Curcumae radix ( ), Endothelium Corneum Gigeriae Galli ( ), Lysimachiae herba ( ), Orthosiphon stamineus ( ) for approximately four months. Neither complications nor side-effects were noted during the CHM treatment. Conclusions: In this case, we concluded that CHM may be an effective alternative therapy for the treatment of ureteral stones, and furthermore, may also be applied as an option to salvage failed ESWL procedures.